Evaluating the Role of Individual Specific Heterogeneity in the Relationship Between Subjective Health Assessments and Income - Iván Fernández-Val; Yevgeniya Savchenko; Francis Vella (Institute for the Study of Labor (IZA), 2013)
This paper investigates the impact of income on an individual's subjective self-assessment of own health. We employ recently developed methods in the non linear panel data literature to account for the endogeneity of income and the presence of individual heterogeneity. We examine a panel data set of individuals living in Australia and find no statistically significant relationship between income and health responses. Moreover, the evidence suggests that the variation in the individual specific effects, comprising both observed and unobserved time invariant factors, is primarily responsible for the variation across individuals' responses.
Keywords: I12; C33; C35; 330; non linear panel data models; subjective health assessments; fixed effects